(untitled) (Revista Iberoamericana de Bioética, 2024)
The essay discusses how digital communication affects scientific research, highlighting how it might increase the scope and effectiveness of the field. It draws attention to how information and communication technologies are being used increasingly for participant recruitment, data gathering, and remote consent. There are ethical challenges mentioned, such as data security and sample representativeness, despite the benefits, such as better access and more openness. Online hiring practices have the potential to exclude people from less developed areas by favoring areas with more internet connection. It is emphasized how crucial it is to protect participants’ privacy and understanding. It is suggested to use a multifaceted method to modify ethical standards for the digital era, incorporating stakeholders and interdisciplinary experts in the creation of targeted regulations. By encouraging moral, open, and inclusive scientific inquiry in the digital era, this strategy hopes to make important scientific advancements.